Academic Performance and Personal and Contextual Dimensions of Socioemotional Learning: Evidence of its Association in Chilean Students - Berger Silva, Christian; Pontificia Universidad Católica de Chile (Pontificia Universidad Javeriana, 2013)
This study supports the growing empirical evidence regarding the relationship between the socioemotional dimension and academic achievement. Through correlation and regression analyses the associations between individual (self-steem and socioemotional well-being) and contextual (perception of the school social climate) features of socioemotional learning and academic success in Chilean elementary students were tested. Socioemotional well-being and perception of school social climate with regards to peer relations and places at school were significantly related to improvements in academic achievement. Results are discussed in terms of their implications for educational practice and future research.